An E-Learning Adaptation of an Evidence-Based Media Literacy Curriculum to Prevent Youth Substance Use in Community Groups: Development and Feasibility of REAL Media - Ray, Anne E (JMIR Form Res, 2019)
BACKGROUND: There is a need for evidence-based substance use prevention efforts that target high school-aged youth that are easy to implement and suitable for dissemination in school and community groups. The Youth Message Development (YMD) program is a brief, four-lesson, in-person curriculum that aims to prevent youth substance use through the development of youth media literacy. Specifically, YMD aims to increase understanding of advertising reach and costs, along with the techniques used to sell products; develop counterarguing and critical thinking skills in response to advertisements; and facilitate application of these skills to the development of youth-generated antisubstance messages. Although YMD has demonstrated evidence of success, it is limited by its delivery method and focus on alcohol and smoking. OBJECTIVE: Study objectives were two-fold: (1) to adapt the YMD curriculum to a self-paced, interactive, electronic-learning (e-learning) format and expand its content to cover alcohol, combustible cigarettes, e-cigarettes, smokeless tobacco, marijuana, and prescription drugs, and (2) to test the feasibility of the adapted curriculum in partnership with a national youth organization. METHODS: An iterative process was employed in partnership with the 4-H youth development organization and a technology developer and consisted of six phases: (1) focus groups to guide adaptation, (2) adaptation to an e-learning format renamed REAL media, (3) pilot-testing of the REAL media prototype to determine feasibility and acceptability, (4) program revisions, (5) usability testing of the revised prototype, and (6) final revisions. Focus groups and pilot and usability testing were conducted with 4-H youth club members and adult club leaders. RESULTS: Focus group feedback guided the build of an e-learning prototype of REAL media, which consisted of five online levels and interactive content guided by a mix of narration and on-screen text. Results of a pilot test of the prototype were neutral to positive, and the program was refined based on end-user feedback. An independent usability test indicated that youth 4-H members felt favorably about navigating REAL media, and they reported high self-efficacy in applying skills learned in the program. Additional refinements to the program were made based on their feedback. CONCLUSIONS: The iterative build process involving the end user from the outset yielded an overall successful technology-driven adaptation of an evidence-based curriculum. This should increase the likelihood of effectively impacting behavioral outcomes as well as uptake within community organizations.